Examining the Export-led Growth Hypothesis: The case of Croatia - Bilas, Vlatka; Bošnjak, Mile; Franc, Sanja (Naše gospodarstvo/Our economy, 2015)
This paper examines the relationship between gross domestic product and exports of goods and services in Croatia between 1996 and 2012. The research results confirmed unidirectional Granger causality from the exports of goods and services to gross domestic product. Following the Engle-Granger approach to cointegration, long-term equilibrium as well as short-term correlation between the observed variables was identified. Exports of goods and services and gross domestic product (GDP) in Croatia move together. If the two observed variables move away from equilibrium, they will return to their long-term equilibrium state at a velocity of 24.46% in the subsequent period. In accordance with the results, we found evidence supporting the export-led growth hypothesis in Croatia. As the outcomes indicated, to recover the economy, Croatia should put more emphasis on the development of exporting sectors.